PERAN LEMBAGA SWADAYA MASYARAKAT DALAM PENANGANAN DAN PERLINDUNGAN ANAK TKI (STUDI KASUS RUMAH PEDULI ANAK TENAGA KERJA INDONESIA) - Sani Salimah Arub; Budi Setiyono; Susilo Utomo (Journal of Politic and Government Studies, 2016)
Abstrack Indonesian Workers pregnant and having childs problems continues to occur each year, along with sending Indonesian workers to destination countries. Worker’s child who takes home are vulnerable to human trafficking issues, many irresponsible people take advantage from the problem, because workers are embarassed to bring the child back to their hometown and it will be a disgrace for them. Sometimes the child is lefted when they just arrived at Soekarno-Hatta International Airport or killed by his own mother. In addition, many of the children who suffer from disorders, mental and physical disabilities. The government is considered less responsive and have not been up to handle the problem or create a policy to prevent migrant workers affected by these problems, marked by continuing reccurence of similar cases every year. Children Care Home for Indonesian Workers or RPATKI is an NGO which is presented in the community to help Indonesian Workers and worker’s child labor. As the shelter and helping the whole process until workers and worker’s child issue is resolved. Uniquely in Indonesia, RPATKI is the only NGO that takes care of and concerned about migrant woekres and child labor migrants. The author takes research on RPATKI because problems of labor migrants and having a child is a real problem and always repeated every year. Along with sending workers abroad and not many people care about the issue when Indonesian workers is one of the heroes of foreign exchange and the marginalized. The research used qualitative research method by using descriptive analytical type. The object of this research is a NGO which is RPATKI and Indonesian workers who are pregnant and have children. The results showed that RPATKI has a role of protection and empowerment role. RPATKI driving factor is the amount of public support both moreal and material, and fill the void role of the state and keep continue to assist migran workers and caring these children to be independent. However, RPATKI also have factors that inhibit them is the closure of Selapajang Return Hall of Indonesian Workers at Soekarno-Hatta International Airport it makes the workers who returned to Indonesia with pregnant and having a child condition is difficult to be monitored because not all of migrant workers have the insight and sufficient information regarding of RPATKI or institution that can help the problems of migrant workers, and lack of coordination, support and good cooperation between NGOs and relevant government authorities. RPATKI have a relationship with the government agency which is BNP2TKI as manifested by the memorandum of understanding entered into between both institutions in supporting RPATKI programs. However, nowadays in practice doesn’t happen any cooperation and relations between these two institutions. Keywords: Non-Governmental Organization, Indonesian Workers, RPATKI